Sensitivity of Neisseria gonorrhoeae to penicillin in West Germany. Issue 2 (April 1979) - Petzoldt, D; Gründer, K; Neubert, U
Abstract : The sensitivity of gonococci to penicillin in Germany has largely decreased in the last 22 years. No significant decrease has occurred, however, in the last three years, but the results show that a slight tendency to decrease may be persisting.